Lutembacher’s Syndrome in a young female treated Surgically: A Case Report (Bangladesh Heart Journal, 2022)
Lutembacher’s syndrome is a rare clinical condition presenting with a combination of congenital atrial septal defect (ASD) and acquired mitral stenosis (MS). Lutembacher’s syndrome is more prevalent in developing countries and its prevalence depends on the prevalence of rheumatic fever in that geographical area. The syndrome can present at any age but is usually more commonly observed in young female adults. Echocardiography remains the gold standard for diagnosis and evaluation of Lutembacher’s syndrome (LS). Now a days many treatment options are available for LS – either percutaneous intervention or surgical correction. But pericardial patch closure of atrial septal defect and prosthetic mitral valve replacement is the treatment of choice for Lutembacher’s syndrome.Bangladesh Heart Journal 2022; 37(2): 143-147